KOMBINASI ALGORITMA VIGENERE CIPHER DAN ONE TIME PAD PADA KEAMANAN CITRA DIGITAL - Riza Maria Ulfa Br Matondang; Achmad Fauzi; Hermansyah Sembiring (STMIK KAPUTAMA, 2021)
The development of the world of technology has made storing and sending digital images easier and more efficient. Problems that arise are issues of information security such as privacy and confidentiality. Images that are stored or distributed in their original form are very vulnerable to wiretapping, theft, and access by unauthorized parties. Image security is carried out using a combination of the vigenere cipher algorithm and the one time pad algorithm, both algorithms are included in symmetric cryptography where the encryption key process is the same as the decryption process. Randomization is done by crossing the process of the two algorithms on the image color pixel row using different keys in each algorithm. The randomization results show that the combination of these two algorithms works well because it will be difficult to break the key compared to using only one algorithm, but the larger the image size, the security system will be the slower the encryption and decryption process will be. The implementation of the security system uses Microsoft Visual Basic 2010 software. The results of this system are in the form of an encrypted image file (ciphercitra) that cannot be understood, then the image file returns to normal after being decrypted.